Differences in farmer’s information consumption and ICT-use – a qualitative research - Csótó, Mihály (Acta Agraria Debreceniensis, 2013)
Farming has now been placed in a new framework: farm managers have had to increasingly devote attention to and interact with the external world. Numerous studies have showed that information and communication technologies (ICT) can play a vital role in realizing benefits with more effective information management at the farm level. Besides land, labour and capital, sufficient information has become a critical factor for agricultural producer. The article presents the findings of a focus-group research which aim was to discover the main characteristics of information consumption and ICT-adoption among Hungarian farmers.